Nutrition Induced Gut Microbiota Modulation in Food Animals: Implications for Viral Susceptibility, Shedding and Transmission Dynamics for Sustainable Development - Md. Emran Hossain (International Journal of Virus Studies, 2026)
The gut microbiota has emerged as a central mediator linking host nutrition, immune competence, and vulnerability to viral pathogens in food animals. Diet is a primary driver of microbial community structure and function, influencing metabolite production, intestinal barrier integrity, and systemic antiviral immunity. Accumulating evidence indicates that nutrition induced modulation of the gut microbiota can substantially alter viral susceptibility, replication, and shedding patterns, with downstream effects on transmission dynamics within and between animal populations. This review synthesizes current knowledge on the tripartite interactions among diet, gut microbiota, and viral infections in major food animal species including poultry, swine, and ruminants. It critically evaluates how macronutrients, micronutrients, and functional feed additives shape microbial ecosystems and related immune pathways that govern host responses to viral challenge. Mechanistic insights into microbiota derived metabolites, mucosal immunity, and gut barrier regulation are integrated with empirical findings on viral load, shedding duration, and environmental persistence. The review further explores how nutrition mediated microbial modulation can be strategically leveraged to reduce disease burden, enhance vaccine responsiveness, and improve farm level biosecurity. Key knowledge gaps are identified, particularly the need for longitudinal, multi-omics, and field-based studies that bridge experimental models with commercial production systems. Overall, this synthesis highlights the potential of precision nutrition and microbiota targeted interventions as sustainable tools to mitigate viral risks while supporting productivity, health, and resilience in food animal production systems
Keywords: Animal Health; Gut microbiota; Nutrition; Sustainability; viral infection; viral shedding; viral transmission